2012
DOI: 10.1097/ta.0b013e31824ac8f5
|View full text |Cite
|
Sign up to set email alerts
|

Injury profiles related to mortality in patients with a low Injury Severity Score

Abstract: Prognostic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(23 reference statements)
0
2
0
Order By: Relevance
“… 31 Joosse et al even identified specific injury profiles of low ISS patients associated with mortality. 32 TEMPT provides benefit early in the course of care and does so independently of retrospective ISS.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Joosse et al even identified specific injury profiles of low ISS patients associated with mortality. 32 TEMPT provides benefit early in the course of care and does so independently of retrospective ISS.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the trauma registry (TR) are also used for a variety of research purposes, such as validation studies (eg, emergency trauma score), retrospective observational or diagnostic research and for calculating the number of additional survivors in a hospital compared with a reference standard (standardised W statistics) 5 6. Accurate and reliable data are vital if meaningful conclusions are to be drawn.…”
Section: Introductionmentioning
confidence: 99%